(untitled) - The World Bank (Washington, D.C., 2008)
The little data book on external debt covers exexternal debt stocks and flows, major economic aggregates, key debt ratios, and the currency composition of long-term debt for allcountries reporting through the debtor reporting system.
Keywords: Debts, External,Công nợ